STRATEGI PENERAPAN SISTEM PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK (E-PROCUREMENT) DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE DI PT. PERTAGAS NIAGA TAHUN 2018 - Saefudin Zuhri; Sofia Ulfa Arrofi U (Prodi Ilmu Politik, 2021)
In order to make the process of procurement of goods and services transparent, the government makes legal rules related to the procurement of goods and services electronically (e-procurement). In line with regulations regarding the procurement of goods and services, the government through the Ministry of SOEs makes regulations regarding the implementation of Good Corporate Governance. Therefore, the formulation of the problem of this research is how to implement strategies for the procurement of goods and serviceselectronically by using an e-procurement system at PT Pertagas Niaga and how the implications of implementing e-procurement in realizing GCG principles. Zarkasyi (2008) mentions 5 (five) GCG principles, there are transparency, accountability, responsibility,independence, fairness. In general, this research aims to determine the related procedures for procurement of goods and services electronically (e-procurement) and to find out the role of e-procurement and a real condition of implementing e-procurement in the procurement of goods and services at PT Pertagas Niaga to realize Good Corporate Governance. This research uses a qualitative approach with descriptive methods and is supported by primary data and secondary data. Data collection technique is by interviewing the procurement function and documentation of related documents. The results showed that the implementation of an electronic procurement of goods and services system using an eprocurement system was effective in realizing Good Corporate Governance because it had met the transparency and information disclosure aspects of PT. Pertagas Niaga